2004
DOI: 10.1089/108497804773391694
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Radionuclide Therapy with 90Y-DOTATOC in Patients with Medullary Thyroid Carcinomas

Abstract: This retrospective analysis is consistent with the literature, regarding a low response rate in medullary thyroid cancers treated with 90Y-DOTATOC. Patients with smaller tumors and higher uptake of the radiopeptide tended to respond better. Studies with 90Y-DOTATOC administered in earlier phases of the disease will help to evaluate the ability of this treatment to enhance survival. New more specific peptides and new isotopes will also represent the key of a better treatment of MTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
56
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(62 citation statements)
references
References 23 publications
3
56
3
Order By: Relevance
“…The use of [ 90 Y-DOTA]-TOC for the treatment of medullary thyroid cancer had previously been described by two pilot studies (11,12). Both studies reported response rates comparable to our results; however, their cohort sizes and extent of follow-up were underpowered to obtain results on survival and its predictors.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The use of [ 90 Y-DOTA]-TOC for the treatment of medullary thyroid cancer had previously been described by two pilot studies (11,12). Both studies reported response rates comparable to our results; however, their cohort sizes and extent of follow-up were underpowered to obtain results on survival and its predictors.…”
Section: Discussionsupporting
confidence: 76%
“…Among other neuroendocrine tumors, medullary thyroid carcinomas express the somatostatin receptor subtype 2, which was initially used for tumor imaging (10). Pilot studies have provided proof of principle that [ 90 Y-DOTA]-TOC treatment could achieve remissions in progressive medullary thyroid cancer (11,12). Herein, we investigated the long-term efficacy and toxicity of [ …”
mentioning
confidence: 99%
“…In recent years many peptide receptor radionuclide therapy (PRRT) clinical trials have been conducted using radiolabelled somatostatin analogues, with promising results [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Based on animal studies and clinical data [6,[14][15][16][17], PRRT is nowadays performed by coinfusion of lysine and arginine for kidney protection. All these data point to the proximal tubule as the main site of kidney uptake, but the specific mechanism of renal uptake has not yet been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is unclear whether the amount of isotope accumulation is sufficient for a therapeutically useful radiation dose. Up to 70% of thyroid cancers express somatostatin receptors, which can be used for treatment with 90 Y-DOTA-Tyr 3 -octreotide (3). At present, the clinical value of this therapy in these patients has not been fully evaluated.…”
mentioning
confidence: 99%